1991
DOI: 10.1002/srin.199100429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structural factors on the creep properties of modified chromium steels

Abstract: The precipitation strengthening of modified chromium steels is effected predominantly by M 23Ce carbides. In molybdenum-modified 9% chromium steels, creep resistance depends on the dispersion of the M 23C 6 carbides and on the molybdenum content in the solid solution. There is no point in increasing molybdenum contents of molybdenum-modified steels above approximately 1 wt. %. In vanadium-modified steels precipitation strengthening is effected both by M 23C e carbides and by VCxN y carbonitrides.If the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Predicted rupture stresses at 600 • C compared to both NIMS data and Al containing steels from COST 538 denoted Bar 257 [16]. that is reported in literature will be evaluated in order to clarify the influence of aluminium [19][20][21]. Work on X20 CrMoV 12 1 steel has confirmed that the rupture strength decreases with aluminium additions [19].…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Predicted rupture stresses at 600 • C compared to both NIMS data and Al containing steels from COST 538 denoted Bar 257 [16]. that is reported in literature will be evaluated in order to clarify the influence of aluminium [19][20][21]. Work on X20 CrMoV 12 1 steel has confirmed that the rupture strength decreases with aluminium additions [19].…”
Section: Methodsmentioning
confidence: 87%
“…that is reported in literature will be evaluated in order to clarify the influence of aluminium [19][20][21]. Work on X20 CrMoV 12 1 steel has confirmed that the rupture strength decreases with aluminium additions [19]. This decrease in rupture strength was up to 30% at 550 • C and 20% at 600 • C. The steel with highest aluminium content showed the presence of coarse AlN of 0.25-1.6 m in size, and it was concluded that these particles cannot contribute to particle strengthening.…”
Section: Methodsmentioning
confidence: 99%
“…8,13) The rotor steel often contains fine M 2 X (mainly Cr 2 N) particles within subgrains. 5,6,8,14,15) HCM12A steel has Cu particles on sub-boundaries.…”
Section: )mentioning
confidence: 99%
“…It has densely populated dislocations while free dislocation density decreases gradually. [1][2][3][4][5][6][7] Since the deterioration of creep strength is accompanied by the loss of dislocation density and subgrain coarsening, the thermal stability of microstructure is of vital importance for heat resistant steels. [6][7][8][9] The microstructural stability of ferritic heat resistant steels is mainly controlled by the thermal stability of precipitates that are able to retard the growth rate of subgrains.…”
Section: Introductionmentioning
confidence: 99%